MIDWIVES’ KNOWLEDGE ON INCREASED WEIGHT GAIN AND AMOUNT OF CALORIE CONSUMPTION IN PREGNANCY: A QUALITATIVE STUDY - Dewi Purwaningsih; Indra Supradewi; Debbyantina Debbyantina (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
This qualitative study provides an illustration that a midwife must follow the recommendations by the International Confederation of Midwives that the care given to the clients must be holistic. This should also occur in the consultation given during the antenatal visit about the ideal range of weight gain for each individual client along with the recommended amount of calorie intake. Therefore, when the two basic kinds of knowledge are less mastered by midwives, the care will be less holistic. Therefore, collaboration with nutritionists can be done when the midwife has detected what has happened to her client. With the correct mastery of competencies, the practice of midwifery care will become holistic and comprehensive.